Unmet Need for Contraception among HIV-Positive Women Attending HIV Care and Treatment Service at Saint Paul’s Hospital Millennium Medical College, Addis Ababa, Ethiopia - Abubeker, Ferid A.; Fanta, Malede B.; Dalton, Vanessa K. (International Journal of Reproductive Medicine, 2019)
Background. The emergence of the HIV epidemic is one of the biggest public health challenges the world has ever seen in recent history. Ethiopia is among the countries most affected by the HIV epidemic. The national estimate for the HIV-positive pregnant women was 24,000 for the year 2016, and there were an estimated 3,800 new HIV infections among children. Regardless of their HIV status contraception offers women, their families, and communities a variety of benefits. For HIV-positive women who do not want to become pregnant, contraception has the added benefit of reducing HIV-positive births. Despite its demonstrable contribution, far less attention has been given to prevention of unintended pregnancy as a strategy to PMTCT. Objectives. To determine the level and contributing factors of unmet need for contraception among HIV-positive women in the ART clinic of Saint Paul’s Hospital Millennium Medical College (SPHMMC). Methods. A facility based cross-sectional study was conducted from 1 September 2016 to 30 November 2016. An exit interview of sampled women enrolled at ART clinic of SPHMMC was done using structured and pretested questionnaire. Descriptive, bivariate, and multivariate methods were used to analyze the level of unmet need and its contributing factors. Results. The overall unmet need for contraception was 25.1%. The most common reasons for nonuse were related to perceived low risk of pregnancy. Unmet need was more common in unmarried women and those who did not discuss about contraception with HIV care provider. Making joint decision on contraceptive utilization with partner and having serodiscordant partner were associated with decreased odds of unmet need. Conclusion. The ART clinic represented one of the missed opportunities to initiate and promote contraceptive use. The study also shows broader demand for contraception and the need for new strategies to address the contraceptive needs among HIV-positive clients.